Clinacanthus nutans Extracts Are Antioxidant with Antiproliferative Effect on Cultured Human Cancer Cell Lines - Yoke, Keong Yong; Jun, Jie Tan; Soek, Sin Teh; Siau, Hui Mah; Cheng, Gwendoline Lian Ee; Hoe, Siong Chiong; Ahmad, Zuraini (Hindawi Publishing Corporation, 2013)
Clinacanthus nutans Lindau leaves (CN) have been used in traditionalmedicine but the therapeutic potential has not been explored for cancer prevention and treatment. Current study aimed to evaluate the antioxidant and antiproliferative effects of CN, extracted in chloroform, methanol, and water, on cancer cell lines. Antioxidant properties of CN were evaluated using DPPH, galvinoxyl, nitric oxide, and hydrogen peroxide based radical scavenging assays, whereas the tumoricidal effect was tested on HepG2, IMR32, NCL-H23, SNU-1, Hela, LS-174T, K562, Raji, and IMR32 cancer cells using MTT assay. Our data showed that CN in chloroform extract was a good antioxidant against DPPH and galvinoxyl radicals, but less effective in negating nitric oxide and hydrogen peroxide radicals. Chloroformextract exerted the highest antiproliferative effect on K-562 (91.28±0.03%) andRaji cell lines (88.97± 1.07%) at 100